Radical Cystectomy Versus Bladder-Preserving Therapy in Muscle-Invasive Bladder Cancer Patients After Nephroureterectomy for Upper Tract Urothelial Carcinoma: A Multicenter Retrospective Analysis - Youngheun Jo; Jun Seok Kim; Yoo Sub Shin; Jongchan Kim; Won Sik Jang; Jee Soo Park; Won Sik Ham (Journal of Urologic Oncology)
Purpose Although radical cystectomy (RC) and concurrent chemoradiotherapy (CCRT) are curative options for muscle-invasive bladder cancer (MIBC), the optimal treatment strategy for MIBC patients with a history of nephroureterectomy for upper tract urothelial carcinoma (UTUC) remains unclear. This retrospective analysis was conducted to compare survival rates and evaluate prognostic factors related to treatment outcomes. Materials and Methods We conducted a multi-institutional retrospective study of patients with MIBC after nephroureterectomy for UTUC between 2005 to 2023. Out of 75 patients, 30 underwent bladder-preserving therapy (BPT), including 22 patients who underwent radiation therapy (RT) and 8 patients who underwent CCRT, while 45 patients underwent RC. The overall survival (OS), cancer-specific survival (CSS), and progression-free survival (PFS) after BPT and RC were evaluated using Kaplan-Meier curves. Cox regression analysis was used to identify variables associated with OS, CSS, and PFS. Posttreatment changes in renal function were compared. Results At 3 years, the OS, CSS, and PFS rates in the BPT group were 52.4%, 71.7%, and 31.3%, respectively, with no significant difference compared to RC. In multivariate analysis, bladder cancer T stage was the only predictive factor for OS, CSS, and PFS. Similar results were also observed in the RT group compared to RC. A significant decrease in renal function was detected among patients in the RC group, while patients in the BPT group maintained preserved renal function. Patients in the BPT group experienced a lower grade of toxicity after treatment compared to those in the RC group, and the rates of survival with functional bladder at 1 year, 3 years, and 5 years were 87.0%, 69.9%, and 69.9%, respectively. Conclusions Bladder-preserving therapy, including RT alone, may be a viable treatment option for patients with MIBC who have undergone nephroureterectomy, as it can achieve comparable oncologic outcomes to RC, while potentially preserving bladder and renal function.